The Influence of Vesicle Size and Composition on α-Synuclein Structure and Stability - Kjaer, Lars (The Biophysical Society, 2009)
Monomeric α-synuclein (αSN), which has no persistent structure in aqueous solution, is known to bind to anionic lipids with a resulting increase in α-helix structure. Here we show that at physiological pH and ionic strength, αSN incubated with different anionic lipid vesicles undergoes a marked increase in α-helical content at a temperature dictated either by the temperature of the lipid phase transition, or (in 1,2-DilauroylSN-Glycero-3-[Phospho-rac-(1-glycerol)] (DLPG), which is fluid down to 0°C) by an intrinsic cold denaturation that occurs around 10–20°C. This structure is subsequently lost in a thermal transition around 60°C. Remarkably, this phenomenon is only observed for vesicles >100 nm in diameter and is sensitive to lipid chain length, longer chain lengths, and larger vesicles giving more cooperative unfolding transitions and a greater degree of structure. For both vesicle size and chain length, a higher degree of compressibility or permeability in the lipid thermal transition region is associated with a higher degree of αSN folding. Furthermore, the degree of structural change is strongly reduced by an increase in ionic strength or a decrease in the amount of anionic lipid. A simple binding-and-folding model that includes the lipid phase transition, exclusive binding of αSN to the liquid disordered phase, the thermodynamics of unfolding, and the electrostatics of binding of αSN to lipids is able to reproduce the two thermal transitions as well as the effect of ionic strength and anionic lipid. Thus the nature of αSN's binding to phospholipid membranes is intimately tied to the lipids' physico-chemical properties.